Aggregation induced emission of gold(i) complexes in water or water mixtures. Issue 34 (11th August 2017) - Pinto, Andrea; Svahn, Noora; Lima, João Carlos; Rodríguez, Laura
Abstract : Gold(i ) complexes are an expanding area of investigation due to the possibility of giving rise to supramolecular aggregates with particular morphologies that can be modulated together with their luminescent properties. Abstract : Gold(i ) complexes are an expanding area of investigation due to the possibility of giving rise to supramolecular aggregates with particular morphologies that can be modulated together with their luminescent properties. A detailed study has been carried out for gold(i ) complexes that self-assemble in aqueous media (in pure water or in mixtures of water and organic solvents in different proportions). The majority of the examples reported until now were found in mixtures of water and DMSO, acetone, DMF or acetonitrile. The addition of cations to a solution of gold(i ) complexes has been observed to show a direct impact on the resulting process of aggregation. The use of perhalogenated ligands together with isocyanide moieties should be highlighted to promote the resulting self-organization. Nevertheless, other ligands like alkynyls or carbenes also promote self-assembly. A careful analysis of the data shows that aurophilic interactions have a key role in the formation of the resulting aggregates and in the enhancement of luminescence (aggregation induced emission, AIE).